Improving Students' Mathematical Representation Ability with E-learning Modules Using the Kvisoft Flipbook Maker Application - Widiani, Tria; Tutut Widiastuti A, T.; Kariadinata, Rahayu (KnE Social Sciences, 2024)
This research is motivated by the need to enhance students’ mathematical representation skills, supported by the findings of a preliminary study involving eighth-grade students at SMPN 2 Gununghalu, West Bandung Regency. In the context of advancing science and technology, one viable approach is to develop technologybased learning media, one of which is by using the Kvisoft Flipbook Maker application. The purpose of this study was to determine whether e-modules, aided by the Kvisoft Flipbook Maker application, could improve students’ mathematical representation skills. The research employed the four-D (4D) research and development method, encompassing four stages: the definition stage, the design stage, the development stage and the dissemination stage. Data collection techniques in this study included both test and non-test methods. The findings from this study revealed an improvement in students’ mathematical representation abilities after utilizing e-modules with the help of the kvisoft flipbook maker application. Additionally, the e-modules met the criteria for validity, effectiveness and practicality in the learning process. Keywords: e-learning modules, kvisoft flipbook, students’ mathematical representation ability.